Regional electron content responses to geomagnetic events at high, middle, and equatorial latitudes obtained by superposed epoch method using AE index - Ratovsky Konstantin; Klimenko Maksim; Vesnin Artem; Belyuchenko Kupriyan (Solar-Terrestrial Physics, 2025)
The paper studies statistical patterns of regional electron content responses to geomagnetic events at high, middle, and equatorial latitudes. The regional electron content is the total electron content averaged over all longitudes in a given latitudinal zone. The statistical analysis includes the following: 1) identification of geomagnetic events based on the AE index and calculation of “reference” geomagnetic storms; 2) calculation of the regional electron content (REC) for five latitudinal zones (equatorial zone, mid-latitude zones of the Northern and Southern hemispheres, and high-latitude zones of the Northern and Southern hemispheres); 3) calculation of REC disturbances (ΔREC), which are relative (percentage) deviations of the observed values, from the 27-day running mean of REC and 4) obtaining the “reference” ionospheric response in the form of the dynamics of average ΔREC, obtained by the superposed epoch method. The superposed epoch method is implemented with the hourly resolution and key moments corresponding to the AE index maximum. Compared with our previous statistical analysis, implemented with daily resolution based on geomagnetic storm identification by the Dst index, the new method leads to a significant increase in the amplitude and the time-focusing of the response. The seasonal behavior of ionospheric responses was analyzed for correspondence to the thermospheric storm concept. The responses of the equatorial and mid-latitude zones of the Southern Hemisphere fit the thermospheric storm concept. In the mid-latitude zone of the Northern Hemisphere, there are a number of exceptions. The responses of the high-latitude zone show the need to take into account the mechanisms behind the formation of positive disturbances, which are absent in the thermospheric storm concept